OP0249 ANTIPHOSPHOLIPID SYNDROME (APS) IN SYSTEMIC LUPUS ERYTHEMATOSUS (SLE) LEADS TO A MORE SEVERE DISEASE. (June 2019) - Riancho-Zarrabeitia, Leyre; Taboada, Victor Martinez; Rua-Figueroa, Iñigo; Sánchez-Alonso, Fernando; Galindo-Izquierdo, María; Ovalles, Juan; Olivé, Alejandro; Fernandez-Nebro, Antonio; Calvo, Jaime; Almagro, Raúl Menor; Muriel, Eva Tomero; Isacelaya, Esther Uriarte; et al.
Abstract : Background: Antiphospholipid antibodies (aPL) have been associated with organ damage and certain features in SLE patients. Objectives: Our aim was to investigate the differences between SLE patients according to the presence of aPL and/or clinical antiphospholipid syndrome. Methods: Patients from the RELESSER-T registry were included. RELESSER-T is a multicenter, hospital-based registry, with retrospective cross-sectional collection of data from a large representative sample of adult non-selected patients with SLE attending Spanish rheumatology services from the public national health system. Results: We included 3651 SLE patients and 1368 were positive for aPL (44.9% of patients were positive for anticardiolipin antibodies, 27.3% showed positivity for anti b2glycoprotein I and 24% for lupus anticoagulant). Overall 2283 patients were classified as SLE no aPL, 528 as SLE-APS and 840 as SLE-aPL. Demographic data, clinical and laboratory features in the different groups are showed in Table 1 . Regarding cardiovascular risk factors, SLE-APS patients had higher rates of hypertension, dyslipidemia and diabetes than SLE-aPL and SLE no aPL patients ( p < 0.001, p < 0.001 and p =0, 022, respectively). SLE-APS patients showed a lower prevalence of photosensitivity and higher frequencies of serositis, proteinuria (>0.5 grs), urinary cell casts, seizures and psychosis ( p ≤0.001). Overall, SLE-APS patients showed a lower rate of cutaneous manifestations and higher rates of neuropsychiatric, cardiac, pulmonary, renal, joint and ophthalmological manifestations (Table 1 ). In accordance with a more severe clinical profile, higher frequency of anti-DNA antibodies and hypocomplementemia were observed in the SLE-APS group ( p <0.001). In addition to a higher disease activity (SLEDAI), SLE APS patients presented more damage accrual with higher values in SLICC (1.9±2.2 in SLE APS, 0.9±1. 4 in SLE aPL and 1.1±1.6, p <0.001) and Katz indexes (3±1.8 in SLE APS, 2.7±1.7 in SLE aPL and 2.6±1.6 in SLE no aPL, p <0.001). Conclusion: SLE-APS patients show a more severe clinical profile with higher frequency of major organ involvement and more damage accrual than SLE-aPL and SLE no APL. Disclosure of Interests: Leyre Riancho-Zarrabeitia Grant/research support from: Abbvie, Pfizer, UCB, MSD, GSK, Amgen, Roche travel grants, Victor Martinez Taboada: None declared, Iñigo Rua-Figueroa: None declared, Fernando Sánchez-Alonso: None declared, María Galindo-Izquierdo: None declared, Juan Ovalles: None declared, Alejandro Olivé Grant/research support from: ND, Consultant for: ND, Paid instructor for: ND, Speakers bureau: ND, Antonio Fernandez-Nebro: None declared, Jaime Calvo Consultant for: Bristol-Myers Squibb, Janssen, Celgene, Sanofi Genzyme, Speakers bureau: Bristol-Myers Squibb, Raúl Menor Almagro: None declared, Eva Tomero Muriel: None declared, Esther Uriarte Isacelaya: None declared, Alina Boteanu: None declared, Mariano Andres: None declared, Mercedes Freire González: None declared, Gregorio Santos Soler: None declared, Esther Ruiz Lucea: None declared, Mónica Ibañez Barceló: None declared, Ivan Castellví Consultant for: I received fees less than 5000USD as a consultant for Kern and Actelion, Paid instructor for: I received fees less than 2000USD as a instructor for Boehringer -Ingelheim, Novartis and Gebro, Speakers bureau: ND, Carles Galisteo: None declared, Víctor Quevedo Vila: None declared, Enrique Raya: None declared, J. Narváez Consultant for: Bristol-Myers Squibb, Lorena Expósito: None declared, José A Hernandez Beriain: None declared, Loreto Horcada: None declared, Jose M Pego-Reigosa: None declared